Histological, cellular and behavioural analyses of effects of chemotherapeutic agent cyclophosphamide in the developing cerebellum. (1st April 2019) - Zhang, Yu; Li, Yongfang; Luo, Wenqin; Tang, Yaohui; Wang, Jia; Yang, Ru; Gao, Wei‐Qiang
Abstract: Objectives: We performed histological, cellular and behavioural analyses of the effects of cyclophosphamide (CTX), a chemotherapeutic drug, in the developing cerebellum and aimed to provide valuable insights into clinical application of CTX in children. Materials and methods: C57BL/6 mice and Math1‐dependent GFP expression transgenic mice were used in the research. H&E staining was performed to analyse histological effects of CTX in the cerebellum. Staining for EdU and TUNEL was used to estimate the cell proliferation and apoptosis. Rotarod test and hanging wire test were used to evaluate the behavioural functions. Immunofluorescent staining was used to identify the cell types. The differentiation markers and genes related to Sonic Hedgehog (SHH) signalling were measured via quantitative real‐time PCR or immunoblotting. Results: We found that while CTX induced a significant reduction in cell proliferation and increased apoptosis in the EGL in 48 hours, the behavioural functions and the multilayer laminar structure of cerebella were largely restored when the mice grew to adults. Mechanistically, granule neuron progenitors, driven by the SHH signalling, enhanced the capability of proliferation quickly after CTX administration was stopped, which allowed the developing cerebellum to catch up and to gradually replenish the injury. Conclusion: The chemotherapeutic agent CTX induces an immediate damage to the developing cerebellum, but the cerebellar multilayer laminar structure and motor function can be largely restored if the agent is stopped shortly after use.